THE VALUE OF HALAL COMMUNICATION AND THE INTEREST OF INDONESIAN MUSLIM UNIVERSITY STUDENTS IN SCARLETT WHITENING AND WARDAH BEAUTY ADVERTISEMENTS ON SOCIAL MEDIA (Karya Ilmiah Mahasiswa (KIMA), 2023)
The aims of this study were: (1) to find out the value of halal communication in scarlett whitening and wardah beauty product advertisements (2) to find out consumer decisions and UMI students' interest in the image of scarlett and wardah products. This study uses a qualitative research type using three ways of collecting observation data, interviews and documentation, with the research approach used is communication, with Roland Barthes theory and New Media theory. The object of this research is at the Indonesian Muslim University Makassar, South Sulawesi. The research method used is descriptive qualitative which aims to answer the formulation of the problem. The results of this study indicate that the value of halal communication is in the form of halal certificates, halal labels and ingredients. Respondents realized that product purchasing decisions were judged by the values ​​and advantages of a product, therefore scarlett and wardah products were very different. The results of the interviews collected by Wardah were more dominant in being chosen by respondents than Scarlett in terms of halal. The advantages of Scarlett are currently triggering consumer interest, especially among teenagers. The appeal of Scarlett's products is that one of the influencers from abroad, namely South Korea, is currently the brand ambassador, namely Soon Jong ki, a top South Korean artist who has become a brand ambassador uploaded on Scarlett Whitening's official Instagram account. The results of the interviews collected by Wardah were more dominant in being chosen by respondents than Scarlett in terms of halal. The advantages of Scarlett are currently triggering consumer interest, especially among teenagers. The appeal of Scarlett's products is that one of the influencers from abroad, namely South Korea, is currently the brand ambassador, namely Soon Jong ki, a top South Korean artist who has become a brand ambassador uploaded on Scarlett Whitening's official Instagram account. The results of the interviews collected by Wardah were more dominant in being chosen by respondents than Scarlett in terms of halal. The advantages of Scarlett are currently triggering consumer interest, especially among teenagers. The appeal of Scarlett's products is that one of the influencers from abroad, namely South Korea, is currently the brand ambassador, namely Soon Jong ki, a top South Korean artist who has become a brand ambassador uploaded on Scarlett Whitening's official Instagram account.